Ipil massacre ; Irreconcilable differences ; Customs S.O.P. [videorecording] - Lazaro, Cheche (The Probe Team)
Tackles the massacre in Zamboanga by the Muslim extremist group; Gancayco Commission's finding on the case of Flor Contemplacion, the reactions of Singaporians and Filipino about the case; and the Probe's hidden camera footage on the anomalies of Bureau of Customs.